History of the Opium problem : The Assault on the East, ca. 1600-195 - Derks, Hans (2012)
Covering a period of about four centuries, this book demonstrates the economic and political components of the opium problem. As a mass product, opium was introduced in India and Indonesia by the Dutch in the 17th century. China suffered the most, but was also the first to get rid of the opium problem around 1950.